Perspectivas da mediação algorítmica na Ciência da Informação - Sousa Junior, Manoel Bezerra de (2024)
The research addresses the interaction between technology, society, and information, with a specific focus on algorithmic mediation, understood as the automated interventions performed by computational algorithms. Its general aim is to investigate how algorithmic mediation is conceptualized both nationally and internationally. In turn, the specific objectives encompass exploring Brazilian scientific production on the topic, analyzing related concepts in national and international scientific works, and investigating the sociotechnical context in which this mediation occurs. The research is grounded in theoretical discussions on technology and society, consolidating the understanding of algorithmic mediation and addressing the main agents of this interaction, such as algorithms, big data, and machine learning. Regarding methodology, the research is basic in nature, with a qualitative approach, exploratory in terms of objectives, and adopting content analysis as the delineation. The selection of documents was carried out through searches for the term "algorithmic mediation"in different academic databases, followed by the use of textual search tools to contextualize the terms found. The results explore national and international academic works on algorithmic mediation and related concepts, contributing to the analysis and synthesis of research data. It concludes that the characterization of algorithmic mediation should consider elements such as non-human agency, automated governance of information, the environment of digital platforms, and automation, which are essential characteristics of this type of mediation.